Polymeric vesicle permeability a facile chemical assay - Battaglia, Giuseppe (Langmuir : the ACS journal of surfaces and colloids, 2006)
We present a simple method to characterize vesicles and determine, at the same time, the membrane permeability to specific molecules. The method is based on encapsulating highly hydrophilic 3,3',3' '-phosphinidynetris-benzenesulfonic acid (PH) into vesicles and subsequently monitoring its reaction with 5,5'-dithiobis-2-nitrobenzoic acid (DTNB). We tested the method by measuring the membrane permeability of vesicles formed from a series of poly(ethylene oxide)-co-polybutylene oxide (EB) copolymers and egg yolk phosphatidylcholine. We found that the experimental data are in good agreement with calculations based on Fick's first law. We therefore quantified the DTNB permeability across vesicle membranes, finding that polymeric EB membranes have a more selective permeability toward polar molecules compared to phospholipids membranes